Strategi Penguatan Manajemen Usaha Pada Usaha Kecil Warung Makan Pak Amin - Rahman, Rahman; Alexandro, Rinto (Journal Pendidikan Ilmu Pengetahuan Sosial, 2025)
Small businesses play a strategic role in driving the people's economy and improving the welfare of local communities. However, most small business actors are still faced with various obstacles, especially in terms of business management that has not been professionally organized. This research focused on Warung Makan Pak Amin as a case study, with the aim of examining the various managerial problems faced and designing a strengthening strategy that is in accordance with field conditions. The research used a descriptive qualitative method with data collection techniques through direct observation, in-depth interviews with owners and employees, and documentation of stall operational activities. The findings showed weaknesses in several important aspects, such as unsystematic financial recording, lack of work structure and division of tasks, and conventional business promotion. Suggested strategies include digitizing financial management, drafting and training work SOPs, and optimizing digital platforms as a means of promotion and customer service. Implementation of these strategies is expected to improve efficiency, productivity, and business sustainability. This study is expected to be a practical reference for other MSME players in building an adaptive management system based on local strengths in the midst of growing economic challenges